Ketoconazole in the treatment of experimental murine paracoccidioidomycosis - Ueda, A. K.; Franco, M.; Fabio, S. A.; Prestes, F. R. (Springer Nature, 1987)
In a murine model of chronic disseminated paracoccidioidomycosis (strain 18; intravenous route), Ketoconazole (200 mg/kg in 0.2% agar) was given daily by gavage in three different schedules. Continuous treatment from an early stage of infection (day 3) up to week 20 was the most effective protocol, leading to remission of histopathological lesions and of both humoral and cellular anti-P. brasiliensis immune response, and clearance of the fungus in lungs; only 1 treated animal at week 20 showed pulmonary granulomas, although less extensive than control mice. Continuous treatment from early stage up to week 8, followed by a 16 week-period of drug discontinuity, caused remission of lesions in all but 3 treated mice which showed active pulmonary paracoccidioidomycosis similar to controls (14.2% of unresponsiveness to treatment). The continuous Ketoconazole protocol since a late stage of infection (week 4) up to week 20 produced a slower remission of lesions and immune response when compared with the first drug schedule. In this model of paracoccidioidomycosis, Ketoconazole showed no detectable side-effects and was a very effective drug especially in a prolonged administration protocol from an early stage of infection.
Keywords: ketoconazole; animal experiment; cellular immunity; drug therapy; experimental infection; fungus; humoral immunity; mouse; mycosis; nonhuman; oral drug administration; paracoccidioides brasiliensis; south american blastomycosis; therapy; Animal; Antigens, Fungal; Ketoconazole; Lung Diseases; Male; Mice; Paracoccidioidomycosis; Support, Non-U.S. Gov't